A Long‐Run Performance Perspective on the Technology Bubble. Issue 2 (2nd April 2018) - Franke, Maximilian; Löffler, Gunter
Abstract: The events surrounding the stock price peak of March 2000 are commonly interpreted as the bursting of a technology or Internet bubble, with some researchers pointing out that the pattern could also arise in fundamental models. We inform the debate by studying the long‐run performance of Internet and technology stocks from March 2000 onward. Using calendar‐time regressions, we do not find conclusive evidence of negative abnormal returns. The results are consistent with a new interpretation of the events; namely, the price drop of the early 2000s was not warranted in light of future cash flows and risk.